Minimum 2 Year Outcomes of a Fixed Bearing Total Ankle Replacement in the United Kingdom. Issue 4 (16th October 2019) - Reeve, William JE; Dearden, Paul; Drake, Benjamin; Kakwani, Rajeshkumar; Aradhyula, Murty N; Talbot, Nicholas; Hughes, Adrian M; Townshend, David; Sharpe, Ian T
Category: Ankle, Ankle Arthritis Introduction/Purpose: The Infinity (Wright medical) total ankle replacement (TAR) has become the most implanted ankle replacement in the UK with a 30.1% share in the most recent 2016 England and Wales NJR 14th report. It is a fixed bearing implant utilising an anterior approach and radiological guidance to aid alignment, and is approved for use in the UK as an uncemented implant. Methods: Since introducing the Infinity TAR in June 2014, all implants from two centres in the UK; The Royal Devon and Exeter Hospital NHS Foundation Trust and Northumbria NHS Healthcare Trust, have been followed up prospectively. 113 implants are included with 2 year minimum follow-up, average follow-up being 33 months (24-52). Pre- and post-operative demographic, radiographic and functional outcomes were collected including Visual Analogue Score (VAS), Manchester Oxford foot questionnaire (MOxFQ, UK validated patient reported outcome score) EQ5D (validated quality of life score). Complexity was assessed using COFAS pre-operative grade. Results: Implant survivorship was 93.8% at 2 years minimum. Median age was 68 (42-92), male: female 72:41. Mean MOxFQ improved by 28, mean EQ5D by 1.4 and mean VAS by 7. 16 cases had planned additional procedures, 5 required intra-operative medial malleolar fixation. There have been 2 revisions for deep infection, 2 for implant subsidence, 1 for instability and 2 for unexplained pain (6.2%). 5 patients have required further surgery to the ankle and hindfoot with implant retention (4.4%). 3 patients have asymptomatic tibial cysts (3.4%) and 1 patient has an asymptomatic talar cyst (0.9%) - there is no evidence of progression or loosening. Conclusion: We report favourable early functional, radiographic and survivorship outcomes of this implant in the UK population.